Theory of Humor and its Classification in Linguistics (Journal of Pedagogical Inventions and Practices, 2023)
Humor is a unique feature of the human mind that allows us to perform a number of functions in society more successfully. Humor allows people to share thoughts and feelings, and to express criticism or displeasure in a socially acceptable way. Thus, for example, humor is used to soften criticism, making it more insulting than direct accusations. Humor facilitates social interaction when sharing unpleasant information. Perception of shared humor allows us to establish and maintain social relationships, which improves mutual understanding between people. With the help of humor, people share their feelings, it should be noted that it is not only positive, but also negative, which is generally not accepted in society. Humor is a special social tool that relieves psychological stress and improves human relationships in general. Obviously, humor helps to socialize.